Pola Penerimaan Mahasiswa Terhadap Presensi RFID STIKOM Surabaya Menggunakan UTAUT 2 Models - Putri, Aulia Maharani; Amelia, Tan; Santoso, Rudi (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
Persence of attending on RFID is one of the media to support learning processin business and informatics institution of Stikom of Surabaya. The application of presence of attending on rfid is expectes can ease college students to do the presence of attending in online before following the subject. However, the utilization of presensi RFID haven’t been tapped optimally by college students. The problem can be solved by doing an evaluation comprehensively and having adequate empirical studies which is suitable with the theory. The theory that is used to know the pattern of Stikom of Surabaya in final assignment, there is unified theory of acceptance and use of technology that is developed by Vanakatesh. UTAUT model has applied in academics by many research. This research found the opposite result of the theory of vankatesh. The four variabels (Performance expectancy, Effort Expectancy, Social Influence and Facilitating Condition) didn’t have positive influence of researcher also didn’t find the positive relation in facilitating condition variabel and habit on the use behavioral intention in using presensi rfid.  Key Words : Students, UTAUT, Performance Expectancy, Presence of attending on RFID